Dampak Tingkat Keyakinan Pelanggan dan Protokol Kesehatan terhadap Keputusan Pembelian di Restoran Hotel Berbintang di Surabaya - Yahya, Ellen Lawrencia; Budidharmanto, Lexi Pranata; Federica, Gabriela (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This study aims to analyze the impact of customer confidence and health protocols on purchasing decisions at three, four, and five-star hotel restaurants in Surabaya. The results indicate that higher customer confidence leads to increased purchasing decisions, higher adherence to health protocols boosts customer confidence, and greater adherence to health protocols results in increased purchasing decisions at Surabaya’s restaurants. Data was collected through structured questionnaires using a combination of open and closed-ended questions, employing the Likert scale, and distributed through social media platforms such as Line, Whatsapp, and Instagram, with 100 respondents sampled using the accidental sampling method. Data analysis was conducted using the Partial Least Square (PLS) method. This research provides insights into the crucial role of customer confidence and health protocols in influencing purchasing decisions at star-rated hotel restaurants in Surabaya, offering valuable guidance to restaurant businesses in understanding customer behavior during the pandemic and improving their strategies to attract more patrons while ensuring their safety and satisfaction.